Use of SPIDER and SPIRE in Image Reconstruction. - Leith, ArDean; Baxter, Bill; Frank, Joachim (International Tables for Crystallography, 2012)
SPIDER is a comprehensive command-operated suite of programs for image processing in electron microscopy, with special emphasis on single-particle reconstruction. This chapter provides an outline of the way SPIDER and SPIRE, its interactive graphical user interface, may be used to obtain a three-dimensional reconstruction from projections of many randomly oriented realizations of a biological molecule.